2010
DOI: 10.1073/pnas.0914605107
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus 12 E4orf6 inhibits ATR activation by promoting TOPBP1 degradation

Abstract: Activation of the cellular DNA damage response is detrimental to adenovirus (Ad) infection. Ad has therefore evolved a number of strategies to inhibit ATM-and ATR-dependent signaling pathways during infection. Recent work suggests that the Ad5 E4orf3 protein prevents ATR activation through its ability to mislocalize the MRN complex. Here we provide evidence to indicate that Ad12 has evolved a different strategy from Ad5 to inhibit ATR. We show that Ad12 utilizes a CUL2/RBX1/elongin C-containing ubiquitin ligas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 37 publications
(64 reference statements)
2
94
0
Order By: Relevance
“…It has been determined, for in-stance, that Ad12 and Ad40 E1B-55K and E4orf6 utilize exclusively the CUL2-containing CRL2 to promote the degradation of p53 during infection, while Ad16 can utilize either CRL2 or CRL5 (10,22). Further investigation has revealed that different Ad serotypes have evolved different strategies in order to neutralize the DNA damage response during infection such that the cohort of substrates targeted for degradation varies between viral serotypes (22,32).…”
mentioning
confidence: 99%
“…It has been determined, for in-stance, that Ad12 and Ad40 E1B-55K and E4orf6 utilize exclusively the CUL2-containing CRL2 to promote the degradation of p53 during infection, while Ad16 can utilize either CRL2 or CRL5 (10,22). Further investigation has revealed that different Ad serotypes have evolved different strategies in order to neutralize the DNA damage response during infection such that the cohort of substrates targeted for degradation varies between viral serotypes (22,32).…”
mentioning
confidence: 99%
“…5,6,9 Similarly, Cul5 NTD expression failed to stabilize Mdm2 and Mdm4 in Ad12-infected cells. In contrast, in Ad5-infected cells, Cul5 NTD expression resulted in reduced levels of Mdm2 (Fig.…”
Section: Shrna-mediated Knockdown Of Mdm2 and Mdm4 Augmentsmentioning
confidence: 99%
“…DNA ligase IV (lig4) 8 and TOPBP1, 6 have been identified, although precise biochemical mechanisms of substrate ubiquitination and degradation for these cellular proteins may differ. 6,9 Mdm2 is RING domain-containing E3 ubiquitin ligase that binds to p53 and mediates its ubiquitination and degradation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations